Pengaruh Ketersediaan Sumber Belajar dan Dukungan Dosen terhadap Motivasi Belajar Bahasa Arab Mahasiswa Pascasarjana UIN Malang - Aini, Nurul; Abidin, Munirul (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
In the learning process, student interaction is not only limited to relationships with teachers, but also involves communication with various other learning resources. Lecturer support and the availability of adequate learning resources are very important to create a pleasant learning environment, because both can increase student learning motivation. This study aims to analyze the effect of the availability of learning resources and lecturer support on the motivation to learn Arabic in Postgraduate students at UIN Malang. This study uses a quantitative approach with a random sampling technique involving 100 students of the Arabic language education study program, class of 2023-2024. Data were collected through a questionnaire with a 5-point Likert scale consisting of 27 question items. Validity and reliability tests were used to analyze the instrument. Then, in data management, the results of the normality test showed a significance value of 0.200, which means the residual distribution is normal. The linearity test showed a significance value of 0.728, which indicates a linear relationship between the independent and dependent variables. The correlation coefficient analysis between the availability of learning resources and lecturer support is r = 0.836, which indicates a very strong positive correlation. The correlation between the availability of learning resources and learning motivation is r = 0.818, while between lecturer support and learning motivation is r = 0.862. Overall, the availability of learning resources and lecturer support contribute 77.5% to the learning motivation of UIN Malang Postgraduate students. This finding provides important implications for the development of learning strategies at the postgraduate level, especially in Arabic language learning at UIN Malang.